Elucidating the effect of potential mitochondrial toxicants on glucose handling and insulin signalling in skeletal muscle and liver cell lines in vitro - Kuretu, Auxiliare (Rhodes University, Faculty of Pharmacy, Pharmacy)
Access restricited. Expected release date 2026.
Keywords: Uncatalogued